Speech Recognition Performance Differences Between Precurved and Straight Electrode Arrays From a Single Manufacturer. Issue 10 (6th December 2022) - Sharma, Rahul K.; Smetak, Miriam R.; Patro, Ankita; Lindquist, Nathan R.; Perkins, Elizabeth L.; Holder, Jourdan T.; Haynes, David S.; Tawfik, Kareem O.
Abstract : Objective: Precurved cochlear implant (CI) electrode arrays have demonstrated superior audiometric outcomes compared with straight electrodes in a handful of studies. However, previous comparisons have often failed to account for preoperative hearing and age. This study compares hearing outcomes for precurved and straight electrodes by a single manufacturer while controlling for these and other factors in a large cohort. Study Design: Retrospective cohort study. Setting: Tertiary academic medical center. Patients: Two hundred thirty-one adult CI recipients between 2015 and 2021 with cochlear (Sydney, Australia) 522/622 (straight) or 532/632 (precurved) electrode arrays. Interventions: Postactivation speech recognition and audiometric testing. Main Outcome Measures: Speech recognition testing (consonant-nucleus-consonant word [CNCw] and AzBio) was collected at 6 and 12 months postactivation. Hearing preservation was characterized by a low-frequency pure-tone average shift, or the change between preoperative and postoperative low-frequency pure-tone average. Results: Two hundred thirty-one patients (253 ears) with 6-month and/or 12-month CNCw or AzBio testing were included. One hundred forty-nine (59%) and 104 (41%) ears were implanted with straight and precurved electrode arrays, respectively. Average age at implantation was 70 years (interquartile range [IQR], 58–77 y). There was no significant difference in mean age between groups. CNCw scores were significantly different ( p = 0.001) between straight (51%; IQR, 36–67%) and precurved arrays (64%; IQR, 48–72%). AzBio scores were not significantly different ( p = 0.081) between straight (72%; IQR, 51–87%) and precurved arrays (81%; IQR, 57–90%). Controlling for age, race, sex, preoperative hearing, and follow-up time, precurved electrode arrays performed significantly better on CNCw (b = 10.0; 95% confidence interval, 4.2–16.0; p < 0.001) and AzBio (b = 8.9; 95% confidence interval, 1.8–16.0;, p = 0.014) testing. Hearing preservation was not different between electrodes on adjusted models. Conclusion: During the study period, patients undergoing placement of precurved electrode arrays had significantly higher CNC and AzBio scores than patients receiving straight electrodes, even after controlling for age, preoperative hearing, and follow-up time. Professional Practice Gap and Educational Need: Understanding the difference in audiometric outcomes between precurved and straight electrode arrays will help to guide electrode selection. Learning Objective: To understand differences in speech recognition scores postoperatively by electrode array type (precurved versus straight). Desired Result: To demonstrate a difference in hearing performance postoperatively by electrode type. Level of Evidence: III Indicate IRB or IACUC: Approved by the Institutional IRB (090155).